Validation of integrated pest management modules for castor (Ricinus communis ) in in Andhra Pradesh - BASAPPA, H (The Indian Journal of Agricultural Sciences, 2011)
An experiment was conducted during 2001-04 to develop and validate location-specific and cost effective integrated pest management modules under real farm situation. Biointensive integrated pest management and chemical insecticide intensive integrated pest management modules were compared with non integrated pest management module 1 (farmers practice with wilt resistant castor variety 'Jyoti') and 2 (farmers practice without 'Jyoti') under farmers conditions in Andhra Pradesh. Both biointensive and chemical insecticide intensive integrated pest management modules were effective in reducing insect pest population compared to non-integrated pest management modules. In the integrated pest management modules average seedling blight and Botrytis incidence ranged from 0.95 to 1.13 and 7.30 to 7.89% compared 6.15-6.95 and 10.43-16.64% in non-integrated pest management modules, respectively. fncidence of Fusariurn wiIt was nil in integrated pest management modules and non-integrated pest management module 1 compared to 24.4 1 % in non-integrated pest management module 2. Average castor seed yield recorded in biointensive integrated pest management module was 519, 536, and 760 kg/ha and cost:benefit ratio was 1:2.49,1:3.17 and 1:3.35, whereas in chemical insecticide intensive integrated pest management module average yield was 529,542 and 767 kg/ha with C:B ratio of 1 :2.26,1:3.04 and I :3.14 compared to non-integrated pest management module 2 with seed yield of 433, 398 and 512 kg/ha and C:B ratio of 1 : 1.78,1;2.2 1 and 1 :2.32 during 2001-02,2002-03 and 2003-04 respectively. Non integrated pest management module1 recorded seed yield of 497 and 630 kg/ha with C:B ratio of 1 :2.82 and 1:2.67 during 2002-03 and 2003-04, respectively.